2019
DOI: 10.1007/s10592-019-01181-5
|View full text |Cite
|
Sign up to set email alerts
|

The role of landscape and history on the genetic structure of peripheral populations of the Near Eastern fire salamander, Salamandra infraimmaculata, in Northern Israel

Abstract: Genetic studies on core versus peripheral populations have yielded many patterns. This diversity in genetic patterns may reflect diversity in the meaning of "peripheral populations" as defined by geography, gene flow patterns, historical effects, and ecological conditions. Populations at the lower latitude periphery of a species' range are of particular concern because they may be at increased risk for extinction due to global climate change. In this work we aim to understand the impact of landscape and ecolog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 69 publications
(62 reference statements)
0
7
1
Order By: Relevance
“…Thus, it seems that migration and dispersal of salamanders is possible through human-mediated landscape structures at low and medium elevations. Our local findings contradict the view that dispersal of S. infraimmaculata is limited through low elevations as found in the range of Galilee (Kershenbaum et al, 2014;Sinai et al, 2019).…”
contrasting
confidence: 99%
See 1 more Smart Citation
“…Thus, it seems that migration and dispersal of salamanders is possible through human-mediated landscape structures at low and medium elevations. Our local findings contradict the view that dispersal of S. infraimmaculata is limited through low elevations as found in the range of Galilee (Kershenbaum et al, 2014;Sinai et al, 2019).…”
contrasting
confidence: 99%
“…Recent genetic population studies revealed a restriction of connectivity between populations in Galilee and Mt. Carmel, possibly driven by land use change, such as settlements and agriculture, and a decrease in genetic diversity towards the southern distribution limit (Blank et al, 2013;Sinai et al, 2019). But the dispersal and migration behaviour of S. infraimmaculata is also strongly restricted by low elevation and steep slope (Kershenbaum et al, 2014;Sinai et al, 2019).…”
mentioning
confidence: 99%
“…Ants, for example, were reported to show local adaptation, even in marginal habitats at their northern range edge (Nguyen et al 2019). Fire salamanders could also adapt to environmentally extreme habitats which were connected to core zones and did show a high genetic diversity (Sinai et al 2019); similar results were found by Schiffers et al (2014).…”
Section: Local Adaptationmentioning
confidence: 76%
“…This step was repeated three times to evaluate if the number of clusters is consistent. Population clustering should be used with caution due to the different assumptions of the programs (Sinai et al, 2019), therefore NetStruct was used as a third method for analyzing the population structure using the network theory (Greenbaum, Templeton, & Bar-David, 2015). After an initial run, the threshold was set between 0.2 and 0.4 and 999 permutations were carried out.…”
Section: Discussionmentioning
confidence: 99%